Poor relief and the Church in Scotland, 1560-1650 - McCallum, John (Historian) (Scottish religious cultures., 2017)
This book sets out the importance of charity in Scottish Reformation studies. Based on extensive archival research involving more than thirty parishes, it sheds new light on the practice of poor relief in the century following the Reformation.